On the optimal design of biased contests - Qiang Fu; Zenan Wu (Theoretical Economics, 2020)
This paper explores the optimal design of biased contests. A designer imposes an identity-dependent treatment on contestants, which varies the balance of the playing field. A generalized lottery contest typically yields no closed-form equilibrium solutions, which nullifies the usual implicit programming approach to optimal contest design and limits analysis to restricted settings. We propose an alternative approach that allows us to circumvent this difficulty and characterize the optimum in a general setting under a wide array of objective functions without solving for the equilibrium explicitly. Our technique applies to a broad array of contest design problems, and the analysis it enables generates novel insights into incentive provision in contests and their optimal design. For instance, we demonstrate that the conventional wisdom of leveling the playing field, which is obtained in limited settings in previous studies, does not generally hold.
Keywords: C72; D72; 330; Contest design; optimal biases; Tullock contest